The prop effects guidebook : lights, motion, sound, and magic - Hart, Eric (Routledge, 2018)
"In The Prop Building Guidebook, author Eric Hart demonstrated how to cut, glue, sculpt, and bend raw materials to build props. Now in The Prop Effects Guidebook, he shows us how to connect and assemble components and parts to make those props light up, explode, make noise, and bleed. It delves into the world of electricity, pneumatics, liquids, and mechanical effects to teach you how to make your props perform magic in front of a live audience. The book is complemented by a companion website featuring videos of how to create individual prop special effects: www.propeffectsguidebook.com."--Provided by publisher